2000
DOI: 10.1515/jpem.2000.13.5.529
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of HbA1c in Intensive Treatment of Children with Type 1 Diabetes

Abstract: Self-control and adjustment of insulin doses to seasonal change need to be improved also in intensively treated children, with regard to the risk for worsened metabolic control after the summer and increased severe hypoglycaemia in spring and early summer. The findings have important implications for design of short-term studies of metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Furthermore, over a 2-year period it has been demonstrated for both hemispheres that in cooler months HbA1c is higher than in warmer months (Higgins et al, 2009). Swedish adults as well as American and Swedish children with T1DM revealed a similar distribution of HbA1c (Asplund, 1997;Hill, Peters, Thompson, Matthews, & Hindmarsh, 2013;Norfeldt & Ludvigsson, 2000) with lower HbA1c in summer than in winter. Children with larger seasonal variations showed an increased risk for SH (Norfeldt & Ludvigsson, 2000).…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, over a 2-year period it has been demonstrated for both hemispheres that in cooler months HbA1c is higher than in warmer months (Higgins et al, 2009). Swedish adults as well as American and Swedish children with T1DM revealed a similar distribution of HbA1c (Asplund, 1997;Hill, Peters, Thompson, Matthews, & Hindmarsh, 2013;Norfeldt & Ludvigsson, 2000) with lower HbA1c in summer than in winter. Children with larger seasonal variations showed an increased risk for SH (Norfeldt & Ludvigsson, 2000).…”
Section: Discussionmentioning
confidence: 79%
“…potentiating insulin resistance). Moreover, it must be appreciated that this seasonal mechanism for regulating metabolism that has been preserved over hundreds of millions of years of evolution is also manifested in man, as multiple studies have clearly demonstrated [66][67][68][69][70][71][72][73][74][75].…”
Section: Role Of the Biological Clock (Scn) And Circadian Rhythms In mentioning
confidence: 99%
“…The following two arguments do, however, speak against the role of vitamin D deficiency as a trigger of ␤-cell autoimmunity: 1) there is a general recommendation that all young children should take daily vitamin D drops in Northern Europe, and this recommendation is implemented by Ͼ95% of the parents, at least in children up to the age of 2 years; and 2) there are regions with a low type 1 diabetes incidence in Northern Europe, e.g., Russian Karelia, having an annual incidence rate of 7.8/100,000 children under the age of 15 years in the time period of 1990 -1999 compared with a rate of 42 in Finland (32). It has been shown that the mean HbA 1c level varies over the year in children with manifest type 1 diabetes, with the highest values in the fall and winter and with lower levels in the spring and summer (33)(34)(35). This may reflect improved insulin sensitivity in the spring and summer because of more physical exercise.…”
Section: Potential Triggers Of ␤-Cell Autoimmunity and Type 1 Diabetesmentioning
confidence: 99%